MANAJEMEN PENGGUNAAN METODE TAHFIZ AL-QUR’AN DI PESANTREN BERBASIS PENDIDIKAN ISLAM TERPADU - Widodo, Wahyudi (STKIP Pesisir Selatan, 2025)
The modernization of the pesantren education system, especially in the form of integrated pesantren, has brought new dynamics in the management of the Qur'an memorization program. This study aims to analyze the management of the use of the Qur'an tahfiz method in integrated Islamic education-based pesantren, focusing on the planning, implementation, and evaluation of the tahfiz program. The research used a qualitative approach with a case study method at Al-Hikmah Integrated Islamic Boarding School. Data collection was carried out through participatory observation, in-depth interviews with pesantren administrators, tahfiz teachers, and students, as well as analysis of tahfiz program documentation. The results showed that effective tahfiz method management includes: systematic planning with gradual memorization targets and structured schedules, implementation of combination methods including talaqqi, tasmi', muroja'ah, and modern technology-based methods, periodic evaluation systems through weekly and monthly memorization exams, and continuous motivation coaching through mentoring programs. This research contributes to the development of a tahfiz management model that integrates classical methods with digital technology and adaptive learning according to the ability of students. This model offers a practical solution for pesantren in optimizing the Qur'an memorization program in the contemporary era, and supports the creation of a more effective, efficient, and sustainable learning process.